Discovery of SARS-CoV-2 inhibitors featuring novel histidine α-nitrile motif - Gone, Nilu Vijay; Enayathullah, Mohammed Ghalib; Thomas, Jessie; Rathee, Parth; Prabhakar, Rajeev; Bokara, Kiran Kumar; Sanjayan, Gangadhar J. (Chemistry and Biodiversity, 2023)
As COVID-19 infection caused severe public health concerns recently, the development of novel antivirals has become the need of the hour. Main protease (Mpro) has been an attractive target for antiviral drugs since it plays a vital role in polyprotein processing and virus maturation. Herein we report the discovery of a novel class of inhibitors against the SARS-CoV-2, bearing histidine alpha-nitrile motif embedded on a simple dipeptide framework. In-vitro and in-silico studies revealed that the histidine alpha-nitrile motif envisioned to target the Mpro contributes to the inhibitory activity. Among a series of dipeptides synthesized featuring this novel structural motif, some dipeptides displayed strong viral reduction (EC50=0.48 mu M) with a high selectivity index, SI>454.54. These compounds also exhibit strong binding energies in the range of -28.7 to -34.2 Kcal/mol. The simple dipeptide structural framework, amenable to quick structural variations, coupled with ease of synthesis from readily available commercial starting materials are the major attractive features of this novel class of SARS-CoV-2 inhibitors. The histidine alpha-nitrile dipeptides raise the hope of discovering potent drug candidates based on this motif to fight the dreaded SARS-CoV-2.
Keywords: dipeptide inhibitors; histidine alpha-nitrile; M-pro (main protease); molecular dynamics; SARS-CoV-2